3x+(k+2)x=1-k

Simple and best practice solution for 3x+(k+2)x=1-k equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x+(k+2)x=1-k equation:


Simplifying
3x + (k + 2) * x = 1 + -1k

Reorder the terms:
3x + (2 + k) * x = 1 + -1k

Reorder the terms for easier multiplication:
3x + x(2 + k) = 1 + -1k
3x + (2 * x + k * x) = 1 + -1k

Reorder the terms:
3x + (kx + 2x) = 1 + -1k
3x + (kx + 2x) = 1 + -1k

Reorder the terms:
kx + 3x + 2x = 1 + -1k

Combine like terms: 3x + 2x = 5x
kx + 5x = 1 + -1k

Solving
kx + 5x = 1 + -1k

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add 'k' to each side of the equation.
kx + k + 5x = 1 + -1k + k

Reorder the terms:
k + kx + 5x = 1 + -1k + k

Combine like terms: -1k + k = 0
k + kx + 5x = 1 + 0
k + kx + 5x = 1

Add '-5x' to each side of the equation.
k + kx + 5x + -5x = 1 + -5x

Combine like terms: 5x + -5x = 0
k + kx + 0 = 1 + -5x
k + kx = 1 + -5x

Reorder the terms:
-1 + k + kx + 5x = 1 + -5x + -1 + 5x

Reorder the terms:
-1 + k + kx + 5x = 1 + -1 + -5x + 5x

Combine like terms: 1 + -1 = 0
-1 + k + kx + 5x = 0 + -5x + 5x
-1 + k + kx + 5x = -5x + 5x

Combine like terms: -5x + 5x = 0
-1 + k + kx + 5x = 0

The solution to this equation could not be determined.

See similar equations:

| -9+4d=9+2d | | 16-6(n)=2+n | | 4.8-1.8=0.4y | | -5*-25=25-10*-25 | | 4n^2-35=-4n | | y=43+-10x | | Y-6.8=7.4 | | -4b+4=2 | | y=-10x+43 | | 2x-11=7x+44 | | 83+(-9)=92 | | 10r=5+9r | | 12x^3/18x^6 | | -6y+33=-9(y-5) | | 7h=6h+3 | | 25+0.25p=60 | | X+2y=471 | | 4x-9y+x-5y+2= | | 13(n-2)=-4(11+m)+1 | | 2(y+8)=5y+28 | | 2x^2-6x+6=18-2x+x^2 | | 6v-1=65 | | 9=q+3 | | 5(c-12)=60 | | 3x+10=r | | 18=-12+0.6z | | 4.17=u/3 | | -5x-30=5(x-4) | | 3x+5=10-1x | | 3y+11=8 | | 14=-16t^2+100 | | 5/6x=-1/12 |

Equations solver categories